Sustainable Tourism Development in the Mandalika Special Economic Zone: A Comprehensive Analysis of Social, Economic, and Environmental Impacts - Zitri, Ilham; Kurniawan, Cahyadi; Joni, Mishan; Harakan, Ahmad (Journal Public Policy, 2025)
This study aims to analyze the implementation of sustainable tourism development in the Mandalika Special Economic Zone (KEK), Central Lombok, and its impacts on social, economic, and environmental aspects. As an area prioritized in the development of super-priority destinations by the Indonesian government, the Mandalika SEZ is an important case study in seeing how the principles of sustainable development are applied in the tourism sector. This study uses a descriptive method with a qualitative approach that relies on secondary data from various previous literature sources, government reports, and relevant documentation. Data analysis was carried out with the help of Nvivo 12 Plus software to group key themes and understand patterns in the data collected. The results of the study show that development in the Mandalika SEZ does not only focus on physical and infrastructure aspects but also includes empowering local communities through strengthening the Micro, Small, and Medium Enterprises (MSMEs) sector, such as agriculture, coffee entrepreneurship, and handicrafts. Tourism has been shown to contribute significantly to local economic growth, creating jobs and increasing community income. This is reflected in the increase in the Human Development Index (HDI) of Central Lombok, which reached 67.57% in 2022. From the environmental side, air and soil quality indicators show significant improvement, with the target of increasing the ecological quality index by 43.31% in 2026, running according to plan, and reaching 43.03% in 2023. Tourism development in the Mandalika Special Economic Zone shows a positive direction in realizing sustainable development. A comprehensive approach to social, economic, and environmental aspects shows that tourism development can be a strategic instrument in improving the quality of life of local communities while preserving the environment.